930. Clinically Significant CMV Infections in Patients with Lymphoma or Multiple Myeloma. (4th December 2021) - Sassine, Joseph; Khawaja, Fareed; Shank, Brandon R; Lovell, Alexandra; Lee, Jenessa; DiPippo, Adam; Rausch, Caitlin R; Spallone, Amy; Heredia, Ella Ariza; Chemaly, Roy F
Abstract: Background: Clinically significant CMV infections (CS-CMVi) among patients with lymphoma and multiple myeloma (MM) have not been clearly defined, especially considering the new cancer therapies that have revolutionized cancer outcomes of these patients. This study aims at describing clinical outcomes of CS-CMVi in this patient population and identify risk factors for CS-CMVi. Methods: This is a single-center, cohort study of all patients with lymphoma and MM who developed CS-CMVi between January 2017 and October 2020. Data was collected from the electronic medical records. CMV outcomes were defined according to the standardized definitions for clinical trials. Data was analyzed on IBM® SPSS version 26 using a logistic regression model for multivariate analysis. Results: We identified 84 patients; 60 (71%) had lymphoma and 24 (29%) had MM (Table 1). CMV end organ disease was diagnosed in 53 (63%) patients as the initial CMV episode and the most common site was the lungs (68%). In our cohort, 25 (30%) patients had autologous HCT and 14 (17%) had CAR T cells infusions prior to CS-CMVi. Recurrent CS-CMVi occurred in 16 (19%) patients (Table 2). A 100-day all-cause mortality was 55%, at a median of 76 days (range 3 -1330 days) after the initial episode of CS-CMVi. CMV related mortality was 11% amongst patients with end organ disease. In multivariate analysis, female gender was associated with a higher risk of CMV end organ disease (OR 3.42, 95% CI 1.14-10.3) and MM with a lower risk of CMV end organ disease compared to lymphoma (OR 0.27, 95% CI 0.07-0.97) (Table 3). Interestingly, 16 (19%) patients received letermovir as secondary prophylaxis for a median of 94 days (range 5 to 339 days) and only 1 patient had recurrent CS-CMVi while on letermovir. Conclusion: CS-CMVi, particularly end organ disease, are not uncommon among patients with lymphoma or MM. Routine CMV surveillance and the use of letermovir for secondary prophylaxis in this patient population should be evaluated in further studies. Disclosures: Fareed Khawaja, MBBS, Eurofins Viracor (Research Grant or Support) Ella Ariza Heredia, MD, Merck (Grant/Research Support) Roy F. Chemaly, MD, MPH, FACP, FIDSA, AiCuris (Grant/Research Support)Ansun Biopharma (Consultant, Grant/Research Support)Chimerix (Consultant, Grant/Research Support)Clinigen (Consultant)Genentech (Consultant, Grant/Research Support)Janssen (Consultant, Grant/Research Support)Karius (Grant/Research Support)Merck (Consultant, Grant/Research Support)Molecular Partners (Consultant, Advisor or Review Panel member)Novartis (Grant/Research Support)Oxford Immunotec (Consultant, Grant/Research Support)Partner Therapeutics (Consultant)Pulmotec (Consultant, Grant/Research Support)Shire/Takeda (Consultant, Grant/Research Support)Viracor (Grant/Research Support)Xenex (Grant/Research Support)